Extent of ESG disclosure for energy sector companies: ESG reporting guide 2.0 Nasdaq - Juli Riyanto Tri Wijaya; Eliada Herwiyanti (Jurnal Akademi Akuntansi)
Purpose: The aim of this research is to assess the extent to which energy sector companies have disclosed ESG-related information in their annual reports in 2021 and 2022.